Preparation Of Activated Carbon From Bamboo Stem Using Microwave Irradiation For Methylene Blue Dye Removal From Aqueous Solution - Sandrasegaran, Navenprasath (Universiti Sains Malaysia, 2018)
A batch process was used to investigate the adsorption of the methylene blue (MB) dye onto bamboo stem based activated carbon (BSAC). In order to prepare the BSAC, bamboo stem (BS) undergoes physical activation process which involves microwave irradiation and carbon dioxide (CO2) gasification. By using response surface methodology (RSM), the optimum preparation conditions were obtained at microwave power and activation time of 440 W and 6.00 minutes respectively which resulted 88.27% MB removal. The optimized sample has high surface area (636.48 m2/g), pore volume (0.4558 cm2/g) and fixed carbon content (75.34%). The pore of BSAC was mesoporous type with average pore diameter of 2.75nm. The effect of initial dye concentration (25-300 mg/L), contact time (0-24 hours) and solution temperature (30-60⁰ C) were also evaluated through. The obtained equilibrium data for MB adsorption by BSAC dye was best fitted by Langmuir model with monolayer maximum adsorption capacity of 222.22 mg/g. Meanwhile, the kinetics data was best represented by the pseudo second-order model. The adsorption process of MB onto BSAC was endothermic and spontaneous process.